The city and its uncertain walls - Murakami, Haruki, 1949-; Gabriel, Philip, 1953- (London : Harvill Secker, 2024)
"The long-awaited new novel from Haruki Murakami, his first in six years, revisits a town his readers will remember, a place where a Dream Reader reviews dreams and where our shadows become untethered from our selves. A love story, a quest, an ode to books and to the libraries that house them, and a parable for these strange post-pandemic times, The City and Its Uncertain Walls is a singular and towering achievement by one of modern literature's most important writers"--
"This is a Borzoi book published by Alfred A. Knopf."
Keywords: Missing persons -- Fiction; Imaginary places -- Fiction; Man-woman relationships -- Fiction; Libraries -- Fiction; First loves -- Fiction; Dreams -- Fiction; Librarians -- Fiction; Library directors -- Fiction; Novels